Metformin, arterial contrast and acute kidney Injury - Lal, Amos; Kaur, Nimal; Trivedi, Nitin (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: We aim to respond to interesting article in your journal by Namazi et al. regarding metformin use in patients undergoing coronary angiography and risk of developing metformin associated lactic acidosis. We share our experience regarding patients using metformin undergoing urgent coronary angiography and risk of developing contrast induced nephropathy. Methods: A retrospective chart review of 154 patients who underwent emergency coronary angiography (CAG) with arterial contrast exposure. The study was approved by the institution review board (Metrowest Medical Center IRB, Framingham Massachusetts, USA). Results: 154 patients admitted with acute coronary syndrome during months of January 2014 – December 2014; 67 patients used metformin (100% had diabetes mellitus) whereas 87 were not on metformin (31% had diabetes mellitus). Our study revealed no difference in contrast induced nephropathy (CIN) between the two groups (p=0.29), when compared at 48 hours after arterial contrast exposure. Higher serum creatinine may be have precluded the use of metformin in the control group. Conclusions: Our single center, small observational study showed no difference in the incidence of CIN in patients who continued to be on metformin after arterial contrast exposure compared to the control group